Procession Of Pujawali Mupuk Kembang At Pura Agung Banjar Adat Gegadon: Hindu Religion Edudcation Values - Ni Made Rai Setyawati; I Made Suastika; Made Iwan Indrawan Jendra (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2018)
One of the ways taken by Hindu people to keep the harmony and prosperity in the world is by performing  yajña. It is being exercised by krama Custom  Banjar of  Gegadon Kapal by conducting a ritual of  pujawali   at the Great Temple of Custom Banjar Gegadon. The temple is a small temple but enthroned by Ida Ratu Gede Sakti. The Pujawali   is performed exactly on the day of budha kliwon wuku Pahang.  This research discusses: (1) The form of procession of Pujawali   Mupuk Kembang  at the Great Temple of Custom Banjar Gegadon, Village of Kapal, District of Mengwi, Regency of  Badung. (2) The function of procession practice of Pujawali   Mupuk Kembang  at the Temple (3) The Hindu religious education valuecontained in the procession.The theories being used in this research includ: 1) Structural functional theory, 2)Religious Theory, 3) Value Theory. The  type  of the research  is descriptive qualitative. The primary sources for the data are  congregation figures,  religious figures andpublic figures, and its secondary sources are in the form of research results of books, articles, which are related with  pujawali   practice. The research instrument is interview guideline by using purposive technique, observation and documentation, the analysis technique, descriptive. The result of the research can be concluded as follows: (1) The procession of  Pujawali   Mupuk Kembang   is a series of  pujawali   ritual from the beginning until the endwhich is closed with nyineb ceremony, (2) The function of  pujawali   consists of education, social, and religious function, (3) The values contained within pujawali   procession is Hindu Religious education values namely tattva, ethic and ceremony.